The Impact of a Change in the Price of VA Health Care on Utilization of VA and Medicare Services. Issue 7 (July 2018) - Nelson, Richard E.; Hicken, Bret; Vanneman, Megan; Liu, Chuan-Fen; Rupper, Randall
Abstract : Introduction: The passage of the Veterans Access, Choice, and Accountability Act of 2014 has expanded the non-Veteran Affairs (VA) care options for eligible US Veterans. In order for these new arrangements to provide the best care possible for Veterans, it is important to understand the relationship between VA and non-VA care options. The purpose of this study was to use another recent VA policy change, one that increased the reimbursement rate that eligible Veterans receive for travel for health care to VA, to understand the use of VA and Medicare services among Medicare-enrolled Veterans. Methods: We used a difference-in-difference technique to compare inpatient and outpatient utilization and cost in VA and Medicare between Veterans who were eligible for travel reimbursement and those who were not eligible following 2 increases in the travel reimbursement rate. We used generalized estimating equation models and 2-part models when cost outcomes were rare. Results: Our cohort consisted of 110, 007 Medicare-enrolled Veterans, including 25, 076 under 65 and 84, 931 over 65 years old. Following the travel reimbursement rate increases, the number of VA outpatient encounters increased for Veterans in our cohort regardless of age group or whether living in an urban or rural area. The number of non-VA outpatient encounters decreased significantly for Veterans in both age groups living in rural areas following these policy changes. Conclusions: Our estimates suggest that VA outpatient care may be a substitute for Medicare outpatient care for Medicare-enrolled Veterans living in rural areas. These results are important because they indicate how Veteran health care utilization might be affected by future policy changes designed to increase access to VA services. They also indicate the ripple effects that may occur in other health systems due to changes in the VA system. Abstract : Supplemental Digital Content is available in the text.